Відділ скіфо-сарматської археології: історія, підсумки, перспективи - Скорий, С.А. (Археологія, 2005)
Статтю присвячено одному з основних наукових осередків вивчення раннього залізного віку в Україні — Відділу скіфо-сарматської археології ІА НАНУ, якому нещодавно виповнилось 60 років. В статье, подготовленной к 60-летию со дня основания одного из основных научных центров по изучению раннего железного века в Украине, излагаются наиболее важные вехи его истории, приводятся малоизвестные факты, значительное внимание отводится теме формирования киевской школы специалистов в области археологии раннего железного века и решающей роли в этом процессе выдающегося ученого — профессора А.И. Тереножкина. Дается оценка научным результатам, полученным учеными Отдела скифо-сарматской археологии ИА НАНУ за последние десятилетия, намечены некоторые ближайшие и перспективные задачи по исследованию памятников скифо-сарматской эпохи в Украине. The article prepared for the 60th anniversary since the foundation of one of the major scientific centers for the study of the Early Iron Age in Ukraine deals with the most significant milestones in its history. The little-known facts are cited, a considerable attention is paid to formation of the Kyiv school of specialists in the area of the Early Iron Age archaeology and to the decisive part played in this process by a prominent scholar— Professor O.I Terenozhkin. The scientific results obtained during the last decades by the scholars of the Scythian and Sarmatian Archaeology Department of IA NASU are evaluated, some immediate and prospective tasks related to the study of Scythian and Sarmatian epoch in Ukraine are outlined.